2011
DOI: 10.1007/s11103-011-9854-1
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic analysis reveals the nature of salinity tolerance of a wheat introgression line

Abstract: The bread wheat cultivar Shanrong No.3 (SR3) is a salinity tolerant derivative of an asymmetric somatic hybrid between cultivar Jinan 177 (JN177) and tall wheatgrass (Thinopyrum ponticum). To reveal some of the mechanisms underlying its elevated abiotic stress tolerance, both SR3 and JN177 were exposed to iso-osmotic NaCl and PEG stress, and the resulting gene expression was analysed using a customized microarray. Some genes associated with stress response proved to be more highly expressed in SR3 than in JN17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 38 publications
4
40
0
Order By: Relevance
“…Note that both of these ROS processing pathways need GSH and NAD(P)H as reducing agents, thereby reducing the GSH/GSSG and NAD(P)H/ NAD(P) + ratios ( Figures 9I to 9K). The efficient antioxidant system ensures redox homeostasis, which can be indicated by the lower malondialdehyde (MDA) content in Ta-sro1 overexpression lines of Arabidopsis under salinity (Supplemental Figure 11), in agreement with that in SR3 (Liu et al, 2012). DNA damage in protoplasts of Arabidopsis plants constitutively expressing Ta-sro1 and VC plants exposed to UV for 30 s, 60 s, and 2 min or 3 mM H 2 O 2 or 5 mM H 2 O 2 as indicated.…”
Section: Ta-sro1 Promotes Growth and Abiotic Stress Tolerance By Regusupporting
confidence: 67%
See 3 more Smart Citations
“…Note that both of these ROS processing pathways need GSH and NAD(P)H as reducing agents, thereby reducing the GSH/GSSG and NAD(P)H/ NAD(P) + ratios ( Figures 9I to 9K). The efficient antioxidant system ensures redox homeostasis, which can be indicated by the lower malondialdehyde (MDA) content in Ta-sro1 overexpression lines of Arabidopsis under salinity (Supplemental Figure 11), in agreement with that in SR3 (Liu et al, 2012). DNA damage in protoplasts of Arabidopsis plants constitutively expressing Ta-sro1 and VC plants exposed to UV for 30 s, 60 s, and 2 min or 3 mM H 2 O 2 or 5 mM H 2 O 2 as indicated.…”
Section: Ta-sro1 Promotes Growth and Abiotic Stress Tolerance By Regusupporting
confidence: 67%
“…A set of 226 genes that were differentially expressed (by at least 2-fold) in SR3 seedlings under stress (200 mM NaCl or 18% PEG) was identified by microarray analysis (Liu et al, 2012). Out of these genes, those related to ROS homeostasis are suggested to play an important role in the generation of the above salinity-tolerant phenotype of cultivar SR3.…”
Section: Isolation Of a Stress-responsive Gene Belonging To The Sro Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Further proteome analysis indicates a better adaptation of the cybrid to cold or drought stress and an upregulated Rubisco activity (wang et al 2010). The complicated regulation mechanism between gene and protein can interfere with downstream hybrid monitoring; Liu et al (2012) demonstrated introgression on the RNA level, but found little correlation between transcriptome and proteome.…”
Section: Characterization Of Somatic Hybridsmentioning
confidence: 99%